Synthesis, and spectral and X-ray structural studies of a novel delocalised triphosphazene (CF3)2PNP(CF3) 2NPPh3 and the triosmium cluster complex Os3(CO)11[(CF3)2PNP(CF3)2NPPh3] - Ang, H.G. (2014)
Journal of Organometallic Chemistry